The subjunctive, a marker of ’subordinance’? A comparison between German and Spanish - Busch, Hans Jörg (Borealis – An International Journal of Hispanic Linguistics, 2014)
Moods as inflectional paradigms can only have a very general value and function, similar to other verbal categories such as tense and aspect. A comparison with German shows that the subjunctive functions as a marker of subordination and signals that the proposition in which it stands is incomplete and must be interpreted with the help of other contextual elements, for example the meaning of the main or matrix verb, a characteristic that has also been called procedural. Therefore only the indicative can be used to express independent statements. All the communicative functions of the subjunctive, for example to express politeness, will be explained as a result of its procedural character. The article clarifies why the subjunctive is also used with factual propositions, for example after verbs of emotions and ‘aunque’. (37,402 characters with spaces)